Rapid Transition to Telehealth Group Exercise and Functional Assessments in Response to COVID-19. (December 2020) - Jennings, Stephen C.; Manning, Kenneth M.; Bettger, Janet Prvu; Hall, Katherine M.; Pearson, Megan; Mateas, Catalin; Briggs, Brandon C.; Oursler, Krisann K.; Blanchard, Erin; Lee, Cathy C.; Castle, Steven; Valencia, Willy M.; et al.
Exercise is critical for health maintenance in late life. The COVID-19 shelter in place and social distancing orders resulted in wide-scale interruptions of exercise therapies, placing older adults at risk for the consequences of decreased mobilization. The purpose of this paper is to describe rapid transition of the Gerofit facility-based group exercise program to telehealth delivery. This Gerofit-to-Home (GTH) program continued with group-based synchronous exercise classes that ranged from 1 to 24 Veterans per class and 1 to 9 classes offered per week in the different locations. Three hundred and eight of 1149 (27%) Veterans active in the Gerofit facility-based programs made the transition to the telehealth delivered classes. Participants' physical performance testing continued remotely as scheduled with comparisons between most recent facility-based and remote testing suggesting that participants retained physical function. Detailed protocols for remote physical performance testing and sample exercise routines are described. Translation to remote delivery of exercise programs for older adults could mitigate negative health effects.